2009
DOI: 10.1179/174328909x435311
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different antioxidants on cure kinetics and aging behaviours of ethylene propylene diene rubber/low density polyethylene blends

Abstract: The aim of this article is to study the effect of antioxidants on cure properties and aging behaviour of ethylene propylene diene rubber (EPDM) and EPDM/low density polyethylene (LDPE) blends. Dicumyl peroxide cured EPDM and EPDM/LDPE blends are prepared with three categories of antioxidants, including: amine, N-isopropyl-N9-phenyl-r-phenylenedia mine (antioxidant 4010NA) and 2,2,4-trimethyl-1,2-dihydroquinoline (antioxidant RD); phenol, n-Otadecyl-b-(4-hydroxy-3,5ditert-butyl-phenyl)-propionate (antioxidant 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The secondary antioxidants convert hydroperoxide to some more stable products, and then, autocatalytic degradation reactions are prevented. 24 For example, the efficiency of phenolic antioxidants has been ascribed to hydrogen bonding between amide groups in polyamides and the hydroxyl groups of the phenolic antioxidants and to the kinetic chain length shown by polyamides. 25,26 In this study, dumbbell-shaped injected samples of PA6/long glass fiber (LGF) were used for the systematic study of thermooxidative aging behaviors; the samples were subjected to oven aging at different times under 160 C. The static and dynamic mechanical properties of the aged PA6/LGF composites were characterized by thermogravimetric analysis, differential scanning calorimetry (DSC), DMA, Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM).…”
Section: Introductionmentioning
confidence: 99%
“…The secondary antioxidants convert hydroperoxide to some more stable products, and then, autocatalytic degradation reactions are prevented. 24 For example, the efficiency of phenolic antioxidants has been ascribed to hydrogen bonding between amide groups in polyamides and the hydroxyl groups of the phenolic antioxidants and to the kinetic chain length shown by polyamides. 25,26 In this study, dumbbell-shaped injected samples of PA6/long glass fiber (LGF) were used for the systematic study of thermooxidative aging behaviors; the samples were subjected to oven aging at different times under 160 C. The static and dynamic mechanical properties of the aged PA6/LGF composites were characterized by thermogravimetric analysis, differential scanning calorimetry (DSC), DMA, Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] These properties have extended its application to thermoplastic vulcanisates, electrical insulation, waterproof rolls and so on.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the majority of antioxidants had the most effective inhibition of peroxide crosslinking reaction. The hardness of these aged EPDM samples containing MBZ/445 behaves similar to each other, because the antioxidant complex has little effect on the peroxide crosslinking reaction of the EPDM . Importantly, the addition of antioxidants improves the antioxidative behaviors of EPDM.…”
Section: Resultsmentioning
confidence: 81%
“…By capturing the free radical, antioxidants hindered the oxidation process during aging. However, it should be noted that free radicals released by peroxide could be consumed by antioxidants, which would affect the mechanical properties of EPDM . In order to investigate the effects of antioxidants on the EPDM gum stocks, the cure property was firstly measured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation